Election Observation in Nigeria and Madagascar: Diplomatic vs. Technocratic Bias - Dirk Kohnert (Review of African Political Economy (ROAPE), 2004)
International election observation has become a valuable means of supporting African democratic polity. Notably, EU observer missions adopting a professional approach are meant to shield against political pressures from partisan stakeholder interests. However, this growing professionalism did not necessarily lead to less biased observation results. Available evidence suggests that in crucial cases, the origin and orientation of the bias changed from 'diplomatic' to 'technocratic'. The latter can be as least as damaging to the declared aims of election observation as the former. Two outstanding examples, the observation of transitional elections in Nigeria and Madagascar, will serve to illustrate this hypothesis and its consequences for the necessary reorientation of election observation methodology. – – RÉSUMÉ "L' observation des élections au Nigeria et à Madagascar: partialité diplomatique versus biais technocratique" - L'observation électorale internationale est devenue un précieux moyens de soutenir des régime démocratique africain. Notamment, les missions d'observation de l'UE, en adoptant une approche professionnelle, sont censés de protéger contre les pressions politiques et des parties prenantes partisanes. Cependant, ce professionnalisme croissant n'a pas nécessairement conduit à des résultats d'observation moins biaisés. Les données disponibles suggèrent que dans des cas cruciaux, l'origine et l'orientation de l'observation biaisée a changé de la partialité « diplomatique » à la partialité « technocratique ». Cette dernier peut être au moins aussi nuisible à l'objectif déclaré de l'observation des élections que l'ancien. Deux exemples remarquables, l'observation des élections de transition au Nigeria et Madagascar, serviront pour fonder cette hypothèse et montre des conséquences pour la réorientation nécessaire de la méthodologie de l'observation des élections.
Keywords: K16; O55; O2; 330; Elections; Election Observation; Madagascar; European Union